Pelatihan Layanan Perjalanan Wisata Berbahasa Inggris Di SMK Negeri 2 Batam - Supardi; Arina Luthfini Lubis; Andri Wibowo; Zaharafatimah (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
We, the academic community from Batam Tourism Polytechnic, do our service because English Travel Service Training is very much needed and useful for those who want to enter the world of work, so all students, especially those majoring in tourism, must take advantage of this training. This service is executed out by attending the location, which is a way of analysis and issue resolution by offering theoretical assistance, which this time took place on May 26 2023 at SMKN 02 Batam and the participants were students of class 11 majoring in tourism at SMKN 02 Batam and teachers as assistants for the Middle School State Vocational No. 2 Batam is a superior, reputable, quality State Tourism School, as well as being a center for tourism education and development which is located on Jalan Pemuda no. 5 Legend of Malacca, Batam Center Kodya Batam Riau Archipelago Province, which has 5 majors namely Accounting Expertise, Department of Tourism Service Business, Hospitality, Culinary, Fashion, Beauty & Spa. This school also has a variety of extracurricular activities such as e-sports, choir, Malay arts, green school, badminton, dance, spirit, scouts, Japanese, English, paskibra, PMR, music and martial arts, so servants are sure to be more This school will excel again if it continues to improve training based on English and tourism awareness.